Gamification of Terror: Bearing Witness to Disciplinary Power in Netflix's Unlocked: A Jail Experiment - Kaczynski, Stephanie (The prison journal, 2025)
This article critically examines Unlocked: A Jail Experiment, a Netflix reality series that documents an unregulated “experiment” at Pulaski County Regional Detention Facility. In the show, the sheriff unlocks cell doors, prompting incarcerated individuals to abruptly transition from 23-hour-per-day lockdown to self-governance. Drawing on Foucault's concept of disciplinary power and Bentham's panopticon, the study argues Unlocked extends carceral surveillance into entertainment, gamifying incarcerated people's lives. Through critical performance ethnography, the analysis highlights how the dangerous new “gamification of terror” genre implicates audiences in co-performative witnessing of carceral violence and raises urgent ethical concerns about media's role in commodifying human suffering.